POVERTY AS SEEN IN EDWARD ALBEE’S THE AMERICAN DREAM - Alfreti A.S. Sumampow; Tini Mogea; Sarah Kamagi (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research is aimed at revealing poverty in Albee’s The American Dream. This research is classified as qualitative research since the data are in the form of words, rather than numbers. Data are taken from primary source, that it the drama itself, and secondary sources which taken from other books and relevant references to support the analysis. In analysing the data, the writer applies objective approach.The result shows that poverty is dominant in this drama. The poverty is lack of food, lack of money, lack of settlement. Lack of food, poverty in The American Dream reflected the low social man described “unemployment”, he has no family and he has bad family background. He has not settlement and he came to Mommy and Daddy apartment for looking status character of Grandma, Mommy, and Young Man. Because when Mommy is young, she lived with Grandma in poor. Everyday Mommy go to school, Grandma wrap a lunch box for Mommy dinner. Lack of money, the Young Man is a man live alone because his mother has died when he was born, and he never known his father. He lived in poor situation or no rank of social life since Young Man, Grandma and Mommy lacks of the economical point which serve to be requirement for the social position. Lack of settlemement, the Young Man is a job and settlement. Grandma is old and she has no settlement, she lives with her daughter and her daughter wants to keep Granda, in nursing house. The impact of poverty for Grandma, Mommy and Young Man is Young Man want do crime just for money, Mommy marry with dady (her husband) just for monery, and Grandma daughter (Mommy) does not respect her.